Unemployment duration, incentives and institutions: A micro-econometric analysis based on Scandinavian data - Knut Røed; Peter Jensen; Anna Thoursie (University of Oslo, Department of Economics, 2002)
Based on a combined register database for Norwegian and Swedish unemployment spells, we use the `between-countries-variation' in the unemployment insurance systems to identify causal effects. The elasticity of the job hazard rate with respect to the benefit replacement ratio is around -1.0 in Norway and -0.5 in Sweden. The limited benefit duration period in Sweden has a large positive impact on the hazard rate, despite generous renewal options through participation in labour market programs. Compulsory program participation seems to operate as a `stick', rather than a `carrot', and is therefore an efficienttool for counteracting moral hazard problems in the benefit system.
Keywords: C41; J64; 330; Unemployment spells; unemployment compensation; non-parametric duration analysis; Arbeitslosigkeit; Dauer; Arbeitslosenversicherung; Konjunktur; Norwegen